The Role of Algorithms in Structuring Online Communities: The Case of Youtube - Barbara CYREK (Communications of International Proceedings, 2021)
The aim of the study is to depict the power of algorithms over online communities on the example of YouTube. Author presents the structure of YouTube community, describing role of algorithms and channel owners in assigning roles. The status of the supporter gives members access to dedicated content. Thus, the elite of the community has greater ability to tighten ties and influence the development of the community. On the other hand, regular members may experience fear of missing out. In the article several concepts of power are presented in the context of the role that algorithms play in online communities. The example of YouTube shows that online communities are increasingly being appropriated by algorithms.
Keywords: Online Communities; Algorithms; Online Social Structure; FOMO